PENGARUH KUALITAS PELAYANAN, CITRA DESTINASI DAN ISLAMIC BRANDING TERHADAP KEPUTUSAN MENGINAP DI HOTEL SYARIAH KOTA PEKANBARU - -, M. Addinul Amri Yuska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This study was conducted to determine the effect of Staying Decisions, Destination Image, and Islamic Branding on Staying Decisions. The population in this study were visitors who were or had stayed at sharia hotels in Pekanbaru City and this research was conducted on sharia horel visitors in Pekanbaru City with 100 respondents. In this study there are four variables, namely three independent variables and one dependent variable. These variables are Service Quality (X1), Destination Image (X2), Islamic Branding (X3), Staying Decisions (Y). In terms of data analysis, this study uses multiple linear regression analysis with the SPSS (Statistical Package for Social Science) application. Based on the hypothesis testing conducted, the study shows that: 1) Service Quality has a positive and significant effect on Staying Decisions; 2) Destination Image has a positive and significant effect on Staying Decisions; 3) Islamic Branding has a positive and significant effect on Staying Decisions;  Keywords: Service quality, Destination Image, Islamic Branding, Staying Decision.